2013
DOI: 10.1155/2013/910104
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Sleep Quality and Consumption of Stimulant Beverages among Patagonian Chilean College Students

Abstract: Objectives. (1) To assess sleep patterns and parameters of sleep quality among Chilean college students and (2) to evaluate the extent to which stimulant beverage use and other lifestyle characteristics are associated with poor sleep quality. Methods. A cross-sectional study was conducted among college students in Patagonia, Chile. Students were asked to complete a self-administered questionnaire to provide information about lifestyle and demographic characteristics. The Pittsburgh Sleep Quality Index (PSQI) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
41
3
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 24 publications
(29 reference statements)
6
41
3
3
Order By: Relevance
“…The study also revealed that 3 out of 10 respondents consumed energy drinks, which is found to be strongly associated with sleep quality. This is in general agreement with prior studies (Aslam et al, 2013;Lemma et al, 2012;Reissig, Strain, & Griffiths, 2009;Velez et al, 2013). Besides caffeine, which is the main stimulant of energy drink, it may also contain other stimulating ingredients.…”
Section: Consumption Of Caffeine Cigarette Smoking and Sleepsupporting
confidence: 93%
See 1 more Smart Citation
“…The study also revealed that 3 out of 10 respondents consumed energy drinks, which is found to be strongly associated with sleep quality. This is in general agreement with prior studies (Aslam et al, 2013;Lemma et al, 2012;Reissig, Strain, & Griffiths, 2009;Velez et al, 2013). Besides caffeine, which is the main stimulant of energy drink, it may also contain other stimulating ingredients.…”
Section: Consumption Of Caffeine Cigarette Smoking and Sleepsupporting
confidence: 93%
“…Present in varying amounts in coffee, energy drinks, tea, soft drinks and even chocolate, it is commonly consumed by young adults. It was found that consumers of any stimulant beverage were 80% more likely to have poor sleep quality than nonconsumers (Velez et al, 2013). Drake et al (Drake, Roehrs, Shambroom, & Roth, 2013) showed that consuming caffeine 0,3 or even 6 hours before bedtime significantly disrupts sleep.…”
Section: Annals Of Psychophysiology Volume 3 October 2016 ©Advance Ementioning
confidence: 99%
“…[1][2][3] In a recent multi-country sleep study, high levels of poor sleep quality were reported among Peruvian, Thai, Ethiopian, and Chilean university students. [4][5][6][7] Each of the populations studied showed associations between poor sleep and the consumption of stimulant beverages. [4][5][6][7] Taylor and Bramoweth 8 found that 60% of university-age students reported consuming stimulant beverages (e.g., sodas and coffee) to combat daytime sleepiness.…”
mentioning
confidence: 99%
“…[4][5][6][7] Each of the populations studied showed associations between poor sleep and the consumption of stimulant beverages. [4][5][6][7] Taylor and Bramoweth 8 found that 60% of university-age students reported consuming stimulant beverages (e.g., sodas and coffee) to combat daytime sleepiness. 8 Approximately 96% of Peruvian medical students reported regular consumption of caffeinated drinks, 9 and 34% of them reported using energy drinks.…”
mentioning
confidence: 99%
“…Sixteen subjects (average age: 36.868.9, 7 males and 9 females) whose PSQI scores were six or greater than six were selected from volunteers recruited for this study. They were suspected to possess some kind of sleep disorder because people with a PSQI score of six or greater than six are classified as poor sleepers (14).…”
Section: Methodsmentioning
confidence: 99%